Effect of using a home-bed mattress on bystander chest compression during out-of-hospital cardiac arrest. Issue 1 (January 2021) - Ahn, Hong Joon; Cho, Yongchul; You, Yeon Ho; Min, Jin Hong; Jeong, Won Joon; Ryu, Seung; Lee, Jin Woong; Cho, Sung Uk; Oh, Se Kwang; Park, Jung Soo; Choi, Younhyuk
Background: Bystander cardiopulmonary resuscitation is a key component of life-saving after an out-of-hospital cardiac arrest. In the pre-arrival instructions for out-of-hospital cardiac arrest, it is recommended that the patient be laid on a flat floor. However, the most common reason for not performing cardiopulmonary resuscitation is that the bystander could not move the patient. Objectives: This study aim to investigate the effects of using a home-bed mattress on the quality of chest compression. Methods: In this prospective, randomized study, chest compression without ventilation was performed for 4 min on a Resusci Anne manikin placed on a flat floor or on three types of home-bed mattresses (hard, medium and soft). Chest compression depth, chest compression rate and chest recoil were measured from the manikin with the Laerdal PC Skill Reporting System, and changes in chest compression quality using the four different surfaces were compared. Results: Thirty participants were enrolled to perform chest compression. There was no significant difference in chest compression depth and depth accuracy between the four surfaces. The median chest compression rates were 108.1 ± 8.5, 107.0 ± 8.3, 103.3 ± 8.9 and 98.3 ± 7.9 compressions/min ( p < 0.001) for the flat floor, hard-, medium-, and soft-firmness mattresses, respectively. Moreover, there was no a significant difference in chest recoil accuracy. Conclusion: Using a home-bed mattress did not decrease the chest compression quality, except chest compression rate of soft-firmness mattress. Thus, it may be effective to initiate chest compression on a home-bed mattress if the bystander cannot move the patient to the floor.